Analisis Postur Kerja Operator Terhadap Risiko MSDs Menggunakan Metode RULA dan REBA Pada Workshop pt. Cosyindo Teknik - Rias Aurelia Syafira Hasan (Fakultas Rekayasa dan Teknologi Industri, 2026)
PT. Cosyindo Teknik is a company that provides mining exploration drilling services, deep wells, as well as geotechnical and hydrological services that has a workshop for drilling equipment maintenance and repair activities. Operator work activities in the workshop are still carried out manually and involve the use of machines, thus potentially causing the risk of Musculoskeletal Disorders (MSDs) due to less ergonomic work postures. This study aims to identify work activities that have the potential to cause unergonomic work postures, analyze the level of ergonomic risk using the Rapid Upper Limb Assessment (RULA) and Rapid Entire Body Assessment (REBA) methods, and provide recommendations for ergonomic improvements to PT. Cosyindo Teknik workshop operators. Data collection was carried out through observation, documentation, and measurement of the operator's work posture angle. The results of the RULA analysis showed that 83% of operators were at a moderate risk level with a score of 3–4 and 17% of operators had a score of 5 which required work posture improvement in the near future. Meanwhile, the results of the REBA analysis showed that all operators had a score of 5–7 which was included in the moderate risk category. The body parts that most frequently exceed the safe limit are the upper arm, lower arm, neck, and trunk. Based on the research results, ergonomic improvements are needed in the form of adjusting the height of the workbench, rearranging the layout of tools and materials, adjusting the position of workpieces, and implementing active rest and periodic stretching to reduce the potential for Musculoskeletal Disorders (MSDs) in workshop operators.